Three-Dimensional Surface Texture Characterization of In Situ Simulated Erosive Tooth Wear. (October 2021) - Hara, A.T.; Elkington-Stauss, D.; Ungar, P.S.; Lippert, F.; Eckert, G.J.; Zero, D.T.
This in situ erosive tooth wear (ETW) study tested enamel 3-dimensional (3D) surface texture outcomes for the detection and differentiation of ETW lesions simulated in clinically relevant conditions. Twenty participants enrolled in this 3-arm crossover intraoral ETW simulation and wore their own partial denture for 14 d holding 2 human enamel specimens (per arm). In each arm, participants were assigned to 1 of 3 different dental erosion protocols: severe (lemon juice/pH 2.5), moderate (grapefruit juice/pH 3.5), and no erosion (bottled drinking water, control). Enamel specimens were evaluated by white-light scanning confocal profilometry for 3D surface texture and surface loss (ETW model validation). Individual point clouds were analyzed using standard dental microwear texture characterization protocols for surface roughness and anisotropy. Fractal complexity ( Asfc ), texture aspect ratio ( Str ), and arithmetical mean height ( Sa ) values were generated at baseline, 7 d, and 14 d. Data were analyzed by analysis of variance models suitable for the crossover design with repeated measurements, and correlation coefficients were used to examine the relationship between outcomes. Asfc and Sa differentiated ETW severity (no erosion < moderate < severe, P < 0.001) at days 7 and 14. Asfc and Sa were lower at baseline compared to days 7 and 14 ( P < 0.001) for moderate and severe challenges. Asfc increased from day 7 to 14 ( P = 0.042) for the severe challenge. For Str, ETW severity did not have a significant effect overall ( P = 0.15). Asfc and Sa were highly positively correlated ( r = 0.89, P < 0.001), while Asfc and Sa were not correlated overall with Str ( r < 0.1, P ≥ 0.25). Enamel surface loss increased with ETW severity (no erosion < moderate < severe, P < 0.001) at days 7 and 14, validating the ETW simulation model. Complexity ( Asfc ) and roughness ( Sa ) outcomes were able to detect and differentiate ETW levels, with Asfc being able to monitor the progression of severe lesions. No clear characterization of ETW lesions could be provided by the anisotropy ( Str ) parameter.